Lecturers’ Knowledge of Social Network Media: Implication for Accessibility and Usability Need in Open and Distance Education - Apata, Funke Susan (West African Journal of Open and Flexible Learning, 2014)
This paper determined the level of lecturers’ knowledge of social network media, the factor which is paramount to accessibility and usability need of the learners in open and distance learning. Population of the study comprised of lecturers in distance learning universities in Nigeria. Out of this population, 80 samples were selected using stratified random sampling from all the schools of the universities. Also, 50 of these lecturers came from single mode university while, the remaining 30 were from dual mode university. Forty-seven were male and 33 were female. The instrument used to obtain data was a self-designed questionnaire with a reliability coefficient of 0.75 using test-retest method. Three research questions and two hypotheses guided the study. Descriptive (mean, frequency count and percentages) were used to analyse the research Questions. The two hypotheses formulated were analysed with t-test statistical analysis. It was discovered that most ODL lecturers only have the knowledge of Facebook. It was, therefore, recommended that ODL lecturers should be given training that is e-leaning- oriented in social network media through, workshop and conferences to better their contribution to accessibility and usability needs of the learners.